ANALISIS PROSES PELAYANAN PELANGGAN DI CALL CENTER MENGGUNAKAN TEORI ANTRIAN UNTUK MENINGKATKAN WAKTU RESPON PADA SAAT DOWN SHIFT DI PT X - Rosida, Alya; Nugrahadi, Bekti; Primasanti, Yunita (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2025)
This study aims to analyze the customer service process at the call center of PT X using queuing theory, especially in dealing with increased workload during downshift. The methods used include field studies, literature studies, operational data collection for three months (September–November), and data processing using QM for Windows V5software. The simulation results show that increasing the arrival rate without adjusting the number of agents causes an increase in waiting time, queues, and server utilization, as well as a decrease in the probability of an empty system. Sensitivity analysis is conducted to evaluate high and low load scenarios, and to determine the optimal number of agents based on thevolume ofincoming calls. This study recommends flexible adjustment of the number of agents, implementation of automation systems, and adaptive shift.